Problematika Pembagian Harta Bersama Pasca Perceraian dan Implikasinya terhadap Hak Kewarisan dalam Perspektif Fiqh Islam - Alfi Syahrin; Annisa Salsabila Nasution; Jasmine Firdaus Harahap; Izdihar Naufal Al Wafi; M. Ryan pasha (Yayasan Dar Arrisyah Indonesia, 2026)
The issue of joint property distribution following divorce remains a significant legal concern in Indonesia, particularly when assets acquired during marriage are transferred to third parties and subsequently affect inheritance distribution. This study aims to analyze the legal status of joint property transferred to third parties after divorce and to examine its implications for inheritance rights from the perspective of Islamic law in Indonesia. The research employs a normative legal method using statutory, conceptual, and case approaches. Primary legal materials include the Marriage Law, the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI), and relevant judicial decisions, while secondary materials consist of scholarly books, journal articles, and legal doctrines. The findings reveal that joint property in Islamic law can be understood through the concept of syirkah (partnership), which recognizes the collective ownership of assets acquired during marriage. Consequently, the unilateral transfer of joint property to third parties without the consent of the other spouse constitutes a violation of the principles of justice, trust, and property protection (ḥifẓ al-māl), and such transfers may be legally challenged and annulled. Furthermore, unresolved disputes concerning joint property create legal uncertainty in inheritance distribution because the portion belonging to the former spouse must first be separated before the deceased’s estate can be distributed to heirs. Therefore, the settlement of joint property disputes serves as a legal prerequisite for the implementation of Islamic inheritance law and functions as an instrument to ensure legal certainty, justice, and the protection of property rights. The study contributes to the development of Islamic family law by demonstrating the interrelationship between post-divorce joint property disputes and inheritance law within the framework of syirkah and maqāṣid al-sharī‘ah.